2015
DOI: 10.1080/09585192.2015.1020447
|View full text |Cite
|
Sign up to set email alerts
|

Impact of individual coping strategies and organisational work–life balance programmes on Australian employee well-being

Abstract: This paper examines several individual coping strategies and employees' perception of organisational provision of work -life balance (WLB) programmes with a sample of 700 Australian employees. The combined effects of individual coping strategies and organisational provision of WLB programmes on employee affective well-being are examined, using structural equation modelling. Results indicate that individuals with positive attitudes and life coping strategies were more capable of achieving overall well-being. Bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(70 citation statements)
references
References 80 publications
2
56
0
Order By: Relevance
“…work-life balance, can be observed (e.g. Adame, Caplliure & Miquel, 2016;Ren & Caudle, 2016;Russo, Shteigman & Carmeli, 2016;Zheng, Kashi, Fan, Molineux & Shan, 2016).…”
Section: Quality Of Life and Work-life Balancementioning
confidence: 99%
“…work-life balance, can be observed (e.g. Adame, Caplliure & Miquel, 2016;Ren & Caudle, 2016;Russo, Shteigman & Carmeli, 2016;Zheng, Kashi, Fan, Molineux & Shan, 2016).…”
Section: Quality Of Life and Work-life Balancementioning
confidence: 99%
“…First, the model proposes that supervisor support influences WFC; in turn, WFC diminishes WLB and job satisfaction. Although these attitudinal consequences (i.e., job satisfaction, WLB, and organizational commitment) are well recognized in management studies, they have not been simultaneously examined as emanating from supervisor support (Drummond et al, 2017; Jenkins, Bhanugopan, & Lockhart, 2016; Mills, Matthews, Henning, & Woo, 2014; Wayne, Casper, Matthews, & Allen, 2013; Zheng, Kashi, Fan, Molineux, & Ee, 2016). Second, the present study expands previous research by linking supervisor support and organizational commitment through a set of variables (WFC, WLB, and job satisfaction) in the context of the Australian financial sector.…”
mentioning
confidence: 99%
“…And positive attitude can positively predict well-being [20]. Our study confirmed and expanded the existing research results in the following ways: Firstly, years of foreign service and number of countries of residence have nothing to do with expatriate SWB, JS, PS and SS; Secondly, SS significantly correlates with expatriate PS negatively, and with their SWB and JS positively; Thirdly, expatriate adjustment can significantly predict SWB and JS positively, and predict PS negatively; Fourthly, spouse adjustment can significantly predict SWB, JS and SS positively, and predict PS negatively.…”
Section: Discussionmentioning
confidence: 99%